The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.29060/taps.2021-7-1/oa2547
|View full text |Cite
|
Sign up to set email alerts
|

Measuring online self-regulated learning among early-career medical doctors in a Massive Open Online Course on COVID-19

Abstract: Introduction: As significant autonomy is given in a Massive Open Online Course (MOOC), online self-regulated learning (SRL) ability is crucial in such courses. We aim to measure the online SRL abilities of early-career medical doctors enrolled in a MOOC. Methods: We performed a cross-sectional study using the Self-Regulated Online Learning Questionnaire-revised version (SOL-Qr). We conducted a three-stage cross-cultural validation of the SOL-Qr, followed by Confirmatory Factor Analysis (CFA). The online SRL ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
1
0
1
Order By: Relevance
“…The relatively high academic workload among clinical year students may also be a factor influencing SRL scores among the two stages of medical education. This is further supported by Greviana et al (9), who reported that a higher workload produces a lower SRL score in internship doctors working inside versus outside the Java-Bali Region. content for the online and blended learning environment with various synchronous activities, the OSLQ developed by Barnard et al (10) was used to analyse students' online SRL profiles.…”
Section: Qualitative Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…The relatively high academic workload among clinical year students may also be a factor influencing SRL scores among the two stages of medical education. This is further supported by Greviana et al (9), who reported that a higher workload produces a lower SRL score in internship doctors working inside versus outside the Java-Bali Region. content for the online and blended learning environment with various synchronous activities, the OSLQ developed by Barnard et al (10) was used to analyse students' online SRL profiles.…”
Section: Qualitative Analysissupporting
confidence: 58%
“…In the online learning setting, the Revised Self-regulated Online Learning Questionnaire (Rev SOL-Q) is a widely used assessment for SRL (8). Recent studies have noted the benefits of Rev SOL-Q in measuring SRL, particularly in Massive Open Online Courses (MOOC), in which students have the full autonomy to control their learning process through self-paced time management (9). Unfortunately, this questionnaire cannot compare some aspects of online learning courses with face-to-face class experiences, such as time management in synchronous courses, classmate interactions and note-taking.…”
mentioning
confidence: 99%
“…Peserta yang bekerja di episentrum utama COVID-19 di negara tersebut menunjukkan skor SRL online yang lebih rendah, sementara peserta yang lulus dari tingkat akreditasi yang lebih tinggi menunjukkan kemampuan manajemen waktu yang lebih baik. (Greviana et al, 2022) Penelitian lain, menerapkan MOOC untuk pembelajaran fisika pada anak SMA.…”
Section: Pendahuluanunclassified